2007
DOI: 10.1002/hon.807
|View full text |Cite
|
Sign up to set email alerts
|

Interpretation of interleukin‐2 receptor alpha positive cells during induction chemotherapy for adult acute myelogenous leukaemia patients

Abstract: To correlate clinical outcomes with the expression of interleukin-2 receptor alpha (CD25) positive cells during induction chemotherapy (IC) in adult patients with acute myeloid leukaemia (AML), we investigated the prognostic importance of subsets of peripheral blood (PB) CD45+CD25+ cells. Seventy-five patients with newly diagnosed AML received the same initial IC; and serial PB samples were taken. The gated CD45/CD25 cell populations were used to compare the intensity of immunophenotypic signals based on the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…[12][13][14] Therefore, many recent clinical studies have relied on PBSCs as a cell source in such cases. Some conflicting results have been reported with respect to chronic GVHD before 2000, when we performed G-CSF-mobilized peripheral blood stem cell transplantation (PBSCT).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[12][13][14] Therefore, many recent clinical studies have relied on PBSCs as a cell source in such cases. Some conflicting results have been reported with respect to chronic GVHD before 2000, when we performed G-CSF-mobilized peripheral blood stem cell transplantation (PBSCT).…”
Section: Discussionmentioning
confidence: 99%
“…Chemotherapy before SCT Since its introduction in 1996, our center's chemotherapy regimen for AML has undergone several modifications that have been documented in previous publications, [12][13][14][15] and all patients enrolled in this study were treated according to the last updated standard protocol. All patients with AML were subjected to the same induction and consolidation strategy.…”
Section: Patientsmentioning
confidence: 99%
“…38 In addition, the evaluation of CD25-positive populations prior, during, and after induction chemotherapy showed that a majority of poorly responding patients demonstrated an increased percentage of CD25-positive cells at day 7 and day 21 after initiation of induction chemotherapy. 39 These clinical results suggest the possibility that chemotherapy may enhance the expression of CD25 in a subset of cells through activation of STAT5 activity and contribute to the subsequent relapse of disease. To determine whether this observation could be recapitulated in an in vitro system, we treated KG1 cells with sub-IC 50 doses of cytarabine and monitored CD25 mRNA expression levels (supplemental Figure 8).…”
Section: Identification Of Aml Cell Lines Sensitive To the Inhibitionmentioning
confidence: 93%
“…All patients were treated according to our center's standard protocol, which consists of 3 × 7 idarubicin (IDA) plus N4‐behenoyl‐1‐β‐D‐arabinofuranosyl cytosine (BH‐AC) induction chemotherapy, as described previously . All patients with non‐APL who achieved first CR received one ( n = 38) or two ( n = 83) more courses of consolidation chemotherapy with the standard regimen at our center.…”
Section: Methodsmentioning
confidence: 99%